PENATAAN KELOMPOK PETANI HUTAN DALAM MELAKSANAKAN AGROFORESTRI UNTUK PEMBERDAYAAN MASYARAKAT DAN PELESTARIAN HUTAN DI KECAMATAN PANTI KABUPATEN PASAMAN - Aldio Surya Dirga (ipdn, 2025)
Agroforestry is implemented with the aim of empowering forest farmer groups in line with forest conservation. Forest area management must be implemented with the correct method to be effective and efficient, and prevent the risk of natural disasters due to environmental damage. This study focuses on the problems faced by farmers in implementing agroforestry, the arrangements needed by forest farmer groups in agroforestry activities in Panti District, and the efforts made by forest farmer groups to run their businesses while protecting forest areas. This study uses a descriptive research method and the data collection techniques used are interviews, documentation, and observation. In this study it is seen that agroforestry activities are not optimal and require the arrangement of farmer groups with the aim of empowering Forest Farmer Groups to be independent, productive, and prosperous and maintain the sustainability of protected forests in Panti District. The arrangement focuses on institutional, administration, and management.